Fertilisasi In Vitro Pada Rahim Manusia Perspektif Al-Qur’an : Aplikasi Teori Tafsir Maqosidi Abdul Mustaqim - Zukhruful, Zukhruful Irbah; Zukhruful Irbah (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Not all married couples are able to have children naturally even though they have had sexual relations. In vitro fertilization techniques are a means to help with this problem. However, there are opinions for and against this effort. The inability of a husband and wife is God's will that must be accepted, so trying to carry out an in vitro fertilization program means not accepting the destiny that God has given. Therefore, starting from this statement, this article will discuss how to understand the verses of the Qur'an related to this phenomenon, especially Surah Al Baqarah verse 223. Researchers are interested in studying using the Tafsir Maqhasidi Abdul Mustaqim approach and using the Library method. Research. The results of this research are in the explanation of Surah Al Baqarah verse 223 that the wife is like a field for cultivating crops and is allowed to be interfered with from any direction through the farji' hole. However, if there is interference with the sexual organs, it will certainly hinder the ability to have offspring. In this case, the fusion of sperm and ovum can be carried out outside the uterus using in vitro fertilization techniques. The efforts carried out through the in vitro fertilization program are related to several maqasid principles, namely hifdz an nasb (protecting offspring), hifdz mal (protecting property), hifdz diin (guarding religion), hifdz aql (protecting reason) and hifz nafs (protecting the soul) .